THE EFFECT OF MELON SEEDS FLOUR (Cucumis Melo L.) TOWARD TOTAL CHOLESTEROL LEVEL IN WHITE MALE WISTAR STRAIN RATS (Rattus Norvegicus) - Maruni Wiwin Diarti; Erlin Yustin Tatontos; Yunan Jiwintarum; Anggun Sari Mianti (poltekkes kemenkes mataram, 2018)
Abstract: Cholesterol is an important element in the body, but in high quantities, it can cause atherosclerosis that will eventually possess an impact on coronary heart disease. One of the foods that can reduce cholesterol is a food contains flavonoids which is found in melon seeds (Cucumis melo l.). It contains high fiber that can reduce either of excessive insulin or blood fat levels. The objective study was to determine the effect of Melon seeds flour Toward Total Cholesterol Level in White Male Wistar Strain Rats. This research was carried out with pre-expriment research design, used One group pretest-postest with 5 male wistar strain rats. Data collected in the form of data examination results of total cholesterol level before and after introducing Melon seeds flour. The mean result of total cholesterol test in white male rats before giving Melon seeds flour was 261 mg / dL, whereas the result of total cholesterol test after giving Melon seeds flour was 190.2 mg/dL. Cholesterol levels decreased by 70.8 mg/dl. In short, presenting Melon seeds flour (Cucumis melo l.) for 14 days can decrease total cholesterol level in white male wistar rats. Keywords: Melon Seeds, wistar strain, total cholesterol.